Pengaruh Kepemimpinan Kepala Sekolah Berbasis Kepemimpinan Demokratis dan Manajemen Berbasis Sekolah Terhadap Peningkatan Mutu Pendidikan di SD Gugus Krueng Raya Kabupaten Aceh Besar - Asmawati, Asmawati; Mardhatillah, Mardhatillah; Musdiani, Musdiani; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the influence of principal leadership and school-based management individually and together on the quality of education at SDN Krueng Raya Aceh Besar Cluster. The type of research used is expost facto to determine the effect of the independent variable on the dependent variable. The study population was 72 teachers and school committee members in SD Cluster. The variables in this study are principal-based leadership democratic leadership (X1), school-based management (X2), and improving the quality of education (Y). The sampling technique uses proportionate simple random sampling, with a selected sample of 80 teachers from 5 elementary schools. Data collection techniques use questionnaires, and the data is analyzed by multiple linear calculations and regression. The research results show that the principal's leadership based on democratic leadership (X1) has a positive effect on improving the quality of education (Y) at the Gugus Krueng Raya Aceh Besar State Elementary School even though it only has a contribution of 0.08%. School-based management (X2) has an effect on improving the quality of education (Y) at the Gugus Krueng Raya Aceh Besar State Elementary School and has a contribution of 15.4%. Principal leadership based on democratic leadership (X1) and school-based management (X2) at Gugus Krueng Raya Aceh Besar State Elementary School contributed 19.01%.